PENGARUH PERTUMBUHAN LABA, KUALITAS AUDIT, PRUDENCE, STRUKTUR MODAL, DAN VOLUNTARY DISCLOSURE TERHADAP KUALITAS LABA: Studi Empiris Pada Perusahaan Indeks Kompas 100 yang terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Dina Rahmawati; Erika Astriani Aprilia (LPPM Universitas Bina Bangsa, 2022)
This study aims to determine the effect of Earnings Growth, Audit Quality, Prudence, Capital Structure, and Voluntary Disclosure on Earnings Quality in Kompas 100 Index companies for the 2016-2020 period. Profit Growth Variable as measured by Profit Growth Index, Audit Quality measured by Dummy Variable, Prudence measured by KNSV, Capital Structure as measured by DER, Voluntary Disclosure as measured by IPS, and Earning Quality as measured by QER. This research is a quantitative study and uses secondary data in the form of annual financial reports from the IDX. The sampling technique in this study used purposive sampling method, obtained 42 companies as research samples. Data analysis tool using software program Eviews version 9. The results show that simultaneously Earnings Growth, Audit Quality, and Voluntary Disclosure have no effect on Earnings Quality, while Prudence and Capital structure has a significant positive effect on Earnings Quality